A preliminary study about the style in "Os sertões" - da Silva, Sueli Maria Ramos; Minussi, Rafael Dias (Laboratório Editorial FCL-UNESP, 2008)
It is the main goal of this study, which has as theoretical background the Greimas’s semiotics and French discourse analysis, the completion of a preliminary research about the style, i.e. ethos, in "Os sertões". Issues relating to genre of discourse, discursive syntax and semantics, notions of textualization – involved in the determination of specific modes of themes and figures combination – as well as the establishment of isotopic contexts will be conducive for us in order to achieve the goal proposed. We aim to highlight that the study of style and genre in "Os sertões" is a complex research that requires great depth. However, this article intends only to lay the foundations for the development of later studies.